Videojuegos: El desafío de un nuevo medio a la Comunicación Social - Gómez García, Salvador (Historia y Comunicación Social, 2007)
The Academia field of computer game research is one of the most promising interdisciplinary areas of research for mass communication researchers. The phenomenon didn’t get attention from academic fields until 20 years ago and, however, need, from social communication point of view, an important theorical effort.
Keywords: Mass Communication History; Videogames; Methodology; Ludology